Genetic diversity among bean landraces and cultivars for agronomy traits and selection of superior parents - Godoy dos Santos, Guilherme (Revista Ciência Agronômica, 2021)
The characterization of genetic diversity in common bean genotypes for various agronomic traits enables the selection of promising parents and the identifi cation of genotypes with high agronomic performance. The present study proposes to evaluate the genetic diversity of common bean landraces and cultivars for 14 agronomic traits; examine the correlations between these traits; defi ne promising crosses; and select genotypes with high agronomic performance. A total of 49 common bean genotypes were evaluated in three growing seasons, consisting of 37 landraces and 12 common bean cultivars. Signifi cant effects of genotype × environment interaction or genotype were observed for all agronomic traits, thereby allowing the study of genetic divergence. Several plant-architecture traits were correlated with each other, whereas grain yield was highly correlated with insertion of the last pod (r = 0.74), number of pods per plant (r = 0.74) and mass of 100 grains (r = - 0.64). The furthest-neighbor method separated the common bean genotypes into two groups, Mesoamerican and Andean, and mass of 100 grains showed the greatest contribution to the differentiation between the genotypes. Tocher’s method was more informative and divided the common bean genotypes into 12 groups. The following crosses are recommended: Vagem Roxa × IPR Juriti, Vagem Roxa × Macanudo, Fepagro Triunfo × IPR Juriti, Fepagro Triunfo × Macanudo, Guapo Brilhante × IPR Juriti, and Guapo Brilhante × Macanudo. The common bean genotypes Fepagro Triunfo, IPR Juriti, Guapo Brilhante, BRS Campeiro and Vagem Roxa have high agronomic performance and should thus be selected by the breeding program.